El aula como un lecho de Procusto: Sofismas y manipulación en enseñanza de Lenguas Extranjeras (2014)
This reflection further expands the philosophical notion of Procrustes’ bed from a sheer critical perspective on curricula design in foreign language teaching. We identify a contradiction amongst intention, design, and usage of such curriculum granted the need of forcing their users to abide by the rules and impositions of the curriculum in order for it to be successful. Little, if any, attention has been paid to learners’ needs or interests. They are however, simply mechanised to serve the method or system, and not, as it should, for the method to serve them. This paper aims at critically considering the inner reasons that stymie the clear communication between learners’ needs and curriculum proposals. The pivotal reason for such lack of communication is self-explanatory from the very layout of most language teaching curricula. The linear presentation content bears no relationship to the expressive possibilities found in the structural randomness of spontaneous speech. To put it simply, the whole fallacy of foreign language teaching rests with the Procrustean philosophy ruling the educational apparatus, viz. students should be subdued to the imposed set of explanations and exercises established a priori by the teacher, the curriculum, the national plan, the department of education, or overseas imported criteria.